2022
DOI: 10.3389/fonc.2022.852348
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Nomogram Based on Multiple-Sequence Magnetic Resonance Imaging Predicts Long-Term Survival in Patients Diagnosed With Nasopharyngeal Carcinoma

Abstract: PurposeAlthough the tumor–node–metastasis staging system is widely used for survival analysis of nasopharyngeal carcinoma (NPC), tumor heterogeneity limits its utility. In this study, we aimed to develop and validate a radiomics model, based on multiple-sequence magnetic resonance imaging (MRI), to estimate the probability of overall survival in patients diagnosed with NPC.MethodsMultiple-sequence MRIs, including T1-weighted, T1 contrast, and T2-weighted imaging, were collected from patients diagnosed with NPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Greater tumor heterogeneity is closely connected with poorer prognosis, which could be only associated with intrinsic aggressive biology or therapy resistance [ 39 ]. We extracted radiomics features from four sequences to construct a prognostic model that may be more comprehensive considering the characteristics of different MRI sequences and exhibited excellent performance for individual prediction [ 40 ]. Wang et al reported that the radiomics model derived from multiple MR sequences had better predictive capability than that derived from a single MR sequence ( p < 0.05) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greater tumor heterogeneity is closely connected with poorer prognosis, which could be only associated with intrinsic aggressive biology or therapy resistance [ 39 ]. We extracted radiomics features from four sequences to construct a prognostic model that may be more comprehensive considering the characteristics of different MRI sequences and exhibited excellent performance for individual prediction [ 40 ]. Wang et al reported that the radiomics model derived from multiple MR sequences had better predictive capability than that derived from a single MR sequence ( p < 0.05) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The allocation of articles from each database and the refinement process to identify relevant studies are detailed in Table S2. After comprehensive analysis, 15 studies were included in our meta-analysis [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], with the exclusion rationale documented in Table S3 [8,10,34,.…”
Section: Study Identification and Selectionmentioning
confidence: 99%